Ambidextrous leadership and individual ambidexterity: emerging challenges for medical representative performance - Muhammad Irfan Nasution; Imas Soemaryani; Yunizar; Hilmiana (Cogent Business & Management, 2024)
Medical Representatives (marketing employees) are spearheads of pharmaceutical company sales. Medical Representative performance directly influences the company's revenue and profitability. With strong sales, companies can grow, compete and generate profits. Understanding Medical Representative performance is the key to ensuring business success and continuity. Therefore, this study examines factors related to Medical Representative performance that can explain the sustainability of pharmaceutical companies in Indonesia. Then, investigate the mediation of work engagement both directly and indirectly. In this research, the elements applied include four aspects, namely ambidextrous leadership, talent management, and individual Ambidexterity. This study uses a quantitative approach. The unit of analysis was also a medical representative in Indonesia, which consisted of 370 subjects in five major cities. Furthermore, the impact analysis method was implemented Structural equation modelling part least square SEM-PLS). The research results show that Ambidextrous Leadership, talent management and individual Ambidexterity directly impact Medical Representative Performance (<0.05); Ambidextrous Leadership, talent management and individual Ambidexterity now impact work engagement (< 0.05). Work engagement influences the performance of Medical Representatives (0.000 < 0.05). Indirectly through mediation, indicating that leadership is ambidextrous, talent management, Individual Ambidexterity influence the performance of Medical Representatives mediated by work engagement (<0.05); Thus, work engagement in this study is a mediating variable with the part mediation category. The results provided new insights for companies to design leadership and medical representative development programs that suit different needs, skills, and expertise in distinct tasks. Work engagement was also promoted among employees to improve Medical Representative performance.Medical representative (Marketing employee) is known to have a central role in the peaceful success of the pharmaceutical company. This study explores the impact of three key e-mails, namely ambidextrous leadership, talent management, and individual ambidexterity, and highlights the role of work engagement mediators. Moreover, the patterns by which people can combine innovation with real action are explained, producing essential adaptations in the ever-changing business world. Medical representatives are also more engaged and enthusiastic about their work due to the exhibition of a strong connection, producing a superior performance. The experiment is subsequently presented in an easy-to-understand language and perspective that benefits anyone from various backgrounds. It also aims to determine the influence of ambidextrous leadership, talent management, individual ambidexterity, and work engagement mediation on medical representative performance.
Keywords: 650; Ambidexterity; organizational behaviour; leadership; engagement